1999
DOI: 10.1530/eje.0.1400362
|View full text |Cite
|
Sign up to set email alerts
|

No loss of sst receptors gene expression in advanced stages of colorectal cancer

Abstract: As demonstrated by several studies, the pan-inhibitory peptide somatostatin (SS) is implicated in a large variety of physiological processes in the gastrointestinal tractus. SS inhibits hormonal and gastric acid secretions, and decreases gastric and intestinal motility, mesenteric blood flow and intestinal absorption. In vitro and in vivo studies showed also that the antiproliferative potency of SS analogs may be a target to improve the prognosis of colorectal cancer. Here we report the expression profile of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Buscail et al (1996) have shown by RT-PCR the expression of hsst2, hsst4 and hsst5 in normal human mucosa. As shown by Laws et al (1997), we demonstrated in a study performed by RT-PCR that all five hsst were detected in normal tissues, hsst5, hsst1 and hsst2 mRNA being the most frequently detectable (Vuaroqueaux et al 1999). These non-quantitative results are in accord with our in situ hybridisation results showing a high expression of hsst5 mRNA in epithelial cells, and of hsst1 mRNA in stroma while hsst2 was found to be widely expressed in mucosa but at a low level.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Buscail et al (1996) have shown by RT-PCR the expression of hsst2, hsst4 and hsst5 in normal human mucosa. As shown by Laws et al (1997), we demonstrated in a study performed by RT-PCR that all five hsst were detected in normal tissues, hsst5, hsst1 and hsst2 mRNA being the most frequently detectable (Vuaroqueaux et al 1999). These non-quantitative results are in accord with our in situ hybridisation results showing a high expression of hsst5 mRNA in epithelial cells, and of hsst1 mRNA in stroma while hsst2 was found to be widely expressed in mucosa but at a low level.…”
Section: Discussionsupporting
confidence: 72%
“…Schematically, sst can activate protein tyrosine phosphatases inducing dephosphorylation of growth factor receptor kinase and then inhibit MAP kinase activity (Pan et al 1992, Buscail et al 1994, Patel & Srikant 1997, Pollak & Schally 1998. Several sst subtypes have been implicated in SS antiproliferative effects (Buscail et al 1994, Sharma et al 1996, 1999, Cordelier et al 1997, Patel & Srikant 1997, Florio et al 1999. Even though SS-induced apoptosis has been shown to occur via the hsst3 subtype in cycling cells (Sharma et al 1996), a large body of experimental evidence suggests involvement of hsst5 in SS-induced antiproliferative effects (Cordelier et al 1997, Sharma et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…When attempting to translate the present findings to clinical settings, it should be considered that studies with somatostatin analogues in patients with advanced colorectal cancer have failed to demonstrate significant benefits (Goldberg et al, 1995), likely as a consequence of a loss of sst receptor expression in patients with lymph node or distant metastases, thus suggesting a possible efficacy of somatostatin only in a limited number of patients with tumours expressing specific sst receptor subtypes. Previous studies have reported a predominance of sst 5 receptor expression in colorectal cancer tissues, in concomitance with a moderate expression of sst 3 receptors (Vuaroqueaux et al, 1999). However, more recent data suggest that all five sst receptor subtypes are involved in colorectal cancer growth and, in particular, that cancer cells lacking sst 3 receptor expression display an enhanced proliferative activity (Qiu et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…These findings are consistent with other investigations indicating the expression of multiple sst receptor subtypes in surgical specimens of human colon cancer. In particular, sst 2 receptors were shown to be almost equally expressed in normal and tumour tissues, with a trend towards receptor loss in malignant cells ( Laws et al ., 1997 ); the presence of sst 1 , sst 3 and sst 4 receptor subtypes was found to be moderate in colon cancer cells ( Laws et al ., 1997 ; Vuaroqueaux et al ., 2000 ), and sst 5 receptor expression was predominant in tumour cells over normal colonic mucosa ( Vuaroqueaux et al ., 1999 , 2000 ). In our cell models, sst 3 receptor protein expression was predominant in Caco‐2 cells, whereas the expression of sst 5 receptors predominated in HT‐29 and HCT116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the aforementioned trials the ssts status of patients has not been elucidated before initiation of therapy, further complicating the interpretation of the findings obtained so far [10]. Regarding this aspect, the few studies that were performed to characterize the pattern of expression of different ssts subtypes in colon cancer have provided controversial results [11][12][13][14], which in our opinion could also be explained by the methods employed. Furthermore, our data on neuroblastoma clearly showed that only a quantitative determination of sst2 gene expression had a significant prognostic value [4].…”
Section: Introductionmentioning
confidence: 99%